2006
DOI: 10.1186/1476-4598-5-30
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Background: Carcinogenesis is a multi-step process indicated by several genes up-or downregulated during tumor progression. This study examined and identified differentially expressed genes in cutaneous squamous cell carcinoma (SCC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 43 publications
2
64
0
Order By: Relevance
“…Thus, in our study, expression patterns detected in MM prone cells from non-lesional areas of the skin were compared with those observed in skin cancer tumors (SCCs and CMs) [35, 36]. Although differences in the experimental designs among studies (normal skin cells vs tumoral tissue or cultured cells vs fresh-frozen tissue) may interfere in the analysis, the expression patterns detected in our study correlate to those observed in skin tumors.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Thus, in our study, expression patterns detected in MM prone cells from non-lesional areas of the skin were compared with those observed in skin cancer tumors (SCCs and CMs) [35, 36]. Although differences in the experimental designs among studies (normal skin cells vs tumoral tissue or cultured cells vs fresh-frozen tissue) may interfere in the analysis, the expression patterns detected in our study correlate to those observed in skin tumors.…”
Section: Discussionmentioning
confidence: 52%
“…To support our hypothesis, the expression pattern of the most deregulated genes in mutant CDKN2A or RHC MC1R variant skin cells was compared to their expression observed in two previously published skin cancer datasets. The GSE2503 dataset contained the whole genome expression of five squamous cell carcinomas (SCCs) and six healthy skin samples[35] and the GSE12391 dataset included 23 melanomas (CMs) at different stages (radial growth phase or vertical growth phase) and 18 common nevi[36]. Due to differences in the array platforms used among the studies, only the expression of genes present in all datasets was evaluated (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SphK1 is also overexpressed in acute leukemia patients [15]. Analyses of microarray data available online (http://www.oncomine.org/, http://www.ncbi.nlm.nih.gov/geo/) show statistically significant increases in SphK1 expression in: N-methyl-N-nitrosourea-induced rat breast cancer model [16]; recurrent breast cancer following tamoxifen therapy [17]; squamous cell carcinoma and it’s precursor actinic keratotic lesions in non-melanoma [18] and melanoma skin cancers [19]; advanced stages of cervical cancer [20]; invasive carcinoma of bladder [21]; oligodendrogliomas [22]; head and neck cancer [23,24]; leukemia, including B- and T-cell acute lymphoblastic leukemia and acute myeloid leukemia [25]; and in adult male germ cell tumors [26] (Fig. 1 ).…”
Section: Sphk1: Expression Activation and Translocationmentioning
confidence: 99%
“…( B ) levels of MTA1 and DNMT3a in cancer cells when compared to the normal cells in Oncomine Cancer Profiling Database. Box’s detail: 1, 10, gastric3940; 2, anaplastic oligodendroglioma41; 3, renal cell carcinoma42, 4–5, Ovarian cell carcinoma43; 6–7, Skin4445 and 8–9, colon cancers46 TCGA Colorectal, 2011]. The p-value is provided for the medium-rank analysis.…”
Section: Figurementioning
confidence: 99%